Brazil : Technical Assistance Report-Strengthening the Framework for Subnational Borrowing. (IMF Staff Country Reports; Country Report ;, 2019)
This Technical Assistance report on Brazil highlights strengthening the framework for substantial borrowing. A significant change in the institutional framework is needed to impose hard budget constraints and promote stable and sustainable policies. The approach proposed in this report is based on demanding greater transparency and accountability by subnational governments, while also making the framework more flexible. If adopted, the framework is expected to introduce risk sharing among states, within an enhanced insolvency framework, and tighten fiscal rules. The proposed changes would also put more emphasis in market incentives. The changes in the framework will also need to be accompanied by progress in addressing fiscal pressures from rising budget rigidities (including pensions) and excessive tax incentives (the so-called tax wars). It is recommended to create an independent fiscal council that monitors fiscal performance and compliance of fiscal rules by subnational governments. One possibility is to add this mandate to the Independent Fiscal Institution, while strengthening its independence and provide enough resources.